Negotiations to improve the Plant Treaty's Multilateral System of Access and Benefit-sharing (a primer for CGIAR staff ) - Halewood, Michael; Lopez Noriega, Isabel (2024)
In 2022, the Governing Body of the International Treaty on Plant Genetic Resources (the Plant Treaty) relaunched international negotiations to improve the multilateral system of access and benefit-sharing. The outcome of these negotiations could have significant impacts on how CGIAR Centers access, manage and distribute crop genetic resources and associated digital sequence information/genomic sequence data (DSI/GSD). In this webinar, the Secretary of the Plant Treaty, Kent Nnadozie, and the two co-chairs of the negotiations, Sunil Archak and Michael Ryan, provided CGIAR leaders and scientists with an update on the state of the negotiations, and highlight opportunities for stakeholders’ engagement in the process.